PENGEMBANGAN MEDIA PRIMAFORM UNTUK MENINGKATKAN KEMAMPUAN PEMECAHAN MASALAH PADA MATERI FPB DAN KPK DI SEKOLAH DASAR - Pasambuna, Sri Yunarni; Abdullah, Gamar; Aries, Nur Sakinah; Marshanawiah, Andi; Arif, Rifda Mardian (SCIENCE : Jurnal Inovasi Pendidikan Matematika dan IPA, 2025)
This study aims to develop Primaform learning media that meets the criteria of feasibility, practicality, and effectiveness in learning Mathematics to improve students' problem-solving abilities in FPB and KPK materials in class V of SDN 9 Kabila. The method used is Research and Development (R&D) with the ADDIE development model, which includes the stages of analyze, design, development, implement, and evaluate. The feasibility of Primaform media was tested through expert validation, with an average percentage result of 89%, which is included in the "Very Feasible" category. The practicality of Primaform media obtained an average percentage score of 96.42% and was categorized as "Very Practical". The effectiveness of the media is seen from the increase in the average value of students from 48.60 (pretest) to 87.47 (posttest), with an NGain Score of 0.76 which is included in the "High" category and a media effectiveness level of 76.11% in the "Effective" category. These results indicate that Primaform media is effective in improving students' problem-solving abilities, which is marked by an increase of 38.87%. In addition, the number of students in the high ability category increased from 1 person (pretest) to 13 people (posttest). ABSTRAKPenelitian ini bertujuan untuk mengembangkan media pembelajaran Primaform yang memenuhi kriteria kelayakan, kepraktisan, dan keefektifan dalam pembelajaran Matematika guna meningkatkan kemampuan pemecahan masalah siswa pada materi FPB dan KPK di kelas V SDN 9 Kabila. Metode yang digunakan adalah Research and Development (R&D) dengan model pengembangan ADDIE, yang meliputi tahap analyze, design, development, implement, dan evaluate. Kelayakan media Primaform diuji melalui validasi ahli, dengan hasil rata-rata presentase sebesar 89%, yang termasuk kategori “Sangat Layak”. Kepraktisan media Primaform memperoleh skor rata-rata presentase 96,42% dan dikategorikan “Sangat Praktis”. Keefektifan media dilihat dari peningkatan nilai rata-rata siswa dari 48,60 (pretes) meningkat menjadi 87,47 (postes), dengan NGain Score sebesar 0,76 yang tergolong dalam kategori “Tinggi” dan tingkat efektifitas media sebesar 76,11% dalam kategori “Efektif". Hasil ini menunjukkan bahwa media Primaform efektif dalam meningkatkan kemampuan pemecahan masalah siswa, yang ditandai dengan peningkatan sebesar 38,87%. Selain itu, jumlah siswa yang masuk pada kategori kemampuan tinggi meningkat dari 1 orang (pretes) menjadi menjadi 13 orang (postes).